Reorientasi Masyarakat Bondowoso Dalam Memilih Lembaga Pendidikan Dasar Islam - Mas'ud Mas'ud; Muhammad Suwignyo Prayogo (Universitas Muhammadiyah Sidoarjo, 2019)
The awareness of Bondowoso society about the importance of education in put their children into quality Islamic education which is labeled as Islamic schools is not an easy thing for parents to do, since the competition for basic Islamic education in the competitive era is more stringent. Hence, this research is conducted based on the academic anxiety about the Islamic educational, that is on the factors that motivate Bondowoso society in choosing representative basic Islamic education and represent advanced school /madrasah in Bondowoso region that is supported by strategies that have been conducted with its contribution to the society. This research is descriptive qualitative research. The object of this research is MI At-Taqwa Bondowoso. In collecting the data, the researcher uses non-participatory observation, in-depth interviews and is equipped with document and literature review. The technique in processing data is by data classification, filtering data, and analysing data by using interactive model of Miles, Huberman and Saldana, namely data condensation, data presentation and drawing conclusions. The results of this study showed that there are many factors which is underlying Bondowoso society in choosing Islamic Education, especially in MI At-Taqwa Bondowoso, they are: 1) religious factors such as character education (both moral and performance), its religious / ubudiyah and its religious knowledge is better; 2) general knowledge factors. MI At-Taqwa is able to prove its various achievements to the public. The Parents' impression of MI At-Taqwa is the institution is able to cover the lessons well between general subjects and Religion, the commitment of educators / teachers in managing education has plus value for parents. While the contributions that have made by the school is the existence of various academic and non-academic achievements that have been produced by MI At-Taqwa as real evidence to the progress of Bondowoso society resources.